THE EFFECTIVENESS OF COMPUTER GAMES IN TEACHING VOCABULARY AT SDN 255 MANCANI - Paldy Paldy (Institut Agama Islam Negeri Palopo, 2013)
The objective of this research were to find out the effectiveness of computer games in teaching vocabulary and to find out the students respons in teaching vocabulary using computer games. This research used total sampling where all of population as sample, there were 30 students.This research used vocabulary test as instrument. In collecting data, this research used some procedures namely pre test, treatment, post test and interview. In pre test and post test used vocabulary test. In pre test the students got score in poor classification namely 63,33 % and 36,66 % got fairly poor and mean score 3,0 (poor). This is implies that the students had low vocabulary. In post test, the students got score in very good classification namely 43,33 %, 30 % got good, and 26,66 % got fairly good and mean score 8,2 (good). This is implies that the students got increasing in vocabulary after treatment. In interview, all of the students gave positive respons of using computer games. Based on the findings and discussion of the study, the writer concludes that the computer games is effective method in teaching vocabulary to the students at SDN 255 Mancani